Determinants of Purchase Intention toward Apple Watch Smartwatch in Bandung City: The role of Perceived Usefulness for Health, Social-Adjustive Function, and Value-Expressive Function - Bintang Samala; Abdul Ahmad Hafidh Nurmansyah (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study examines how perceived usefulness for health (PUFH), social-adjustive function (SAF), and value-expressive function (VEF) affect purchase intentions regarding Apple Watch products in Bandung. The research addresses fluctuating consumer interest, as the Apple Watch, though a market leader, has seen a decline in the Top Brand index. A quantitative survey was administered to 124 purposively selected participants who were at least 17 years old and had prior familiarity with Apple Watch products. The dataset was evaluated through multiple linear regression using SPSS version 25. All independent variables showed positive and statistically significant effects on purchase intention, both separately and jointly. VEF emerged as the most influential predictor, followed by PUFH and SAF. These findings suggest that both functional health benefits and the motivations for self-expression and social approval shape consumers' decisions to purchase an Apple Watch. This research strengthens the combined application of the Technology Acceptance Model and the Functional Theory of Attitudes. Applying these frameworks to wearable technology research provides practical insights for marketing strategies that address functional, social, and self-expressive considerations.